Chromosomal microarrays testing in children with developmental disabilities and congenital anomalies - Guillermo Lay-Son; Karena Espinoza; Cecilia Vial; Juan C. Rivera; María L. Guzmán; Gabriela M. Repetto (Elsevier, 2015)
Objectives: Clinical use of microarray-based techniques for the analysis of many developmental disorders has emerged during the last decade. Thus, chromosomal microarray has been positioned as a first-tier test. This study reports the first experience in a Chilean cohort. Methods: Chilean patients with developmental disabilities and congenital anomalies were studied with a high-density microarray (CytoScan™ HD Array, Affymetrix, Inc., Santa Clara, CA, USA). Patients had previous cytogenetic studies with either a normal result or a poorly characterized anomaly. Results: This study tested 40 patients selected by two or more criteria, including: major congenital anomalies, facial dysmorphism, developmental delay, and intellectual disability. Copy number variants (CNVs) were found in 72.5% of patients, while a pathogenic CNV was found in 25% of patients and a CNV of uncertain clinical significance was found in 2.5% of patients. Conclusion: Chromosomal microarray analysis is a useful and powerful tool for diagnosis of developmental diseases, by allowing accurate diagnosis, improving the diagnosis rate, and discovering new etiologies. The higher cost is a limitation for widespread use in this setting. Resumo: Objetivo: O uso clínico de técnicas baseadas em microarrays para a análise de transtornos de desenvolvimento tem surgido durante a última década. Assim, o microarray cromossômico tem sido posicionado como um teste de primeiro nível clínico. Relatamos a primeira experiência em uma coorte chilena. Métodos: Pacientes chilenos com atraso de desenvolvimento e anomalias congênitas foram estudados com um microarray de alta densidade (CytoScan™ HD Array, Affymetrix, Inc., Santa Clara, CA, EUA). Pacientes tiveram estudos citogenéticos anteriores, ou um resultado normal ou de uma anomalia não bem caracterizada. Resultados: Foram analisados 40 pacientes selecionados por dois ou mais critérios, incluindo: anomalias congênitas maiores, dismorfismo facial, atraso de desenvolvimento e deficiência intelectual. Uma variante do número de cópia (CNV) foi encontrada em 72,5% dos pacientes, enquanto que uma CNV patogênica foi encontrada em 25% dos pacientes e uma CNV de significado clínico incerto foi encontrada em 2,5% dos pacientes. Conclusões: A análise cromossômica microarray é uma ferramenta útil e poderosa em transtornos de desenvolvimento, permitindo um diagnóstico preciso, melhorando a taxa de diagnóstico, e descobrindo novas etiologias. O custo mais elevado é uma limitação para um uso difundido em nossa realidade. Keywords: Microarrays, Congenital anomalies, Developmental disabilities, Copy number variants, Diagnosis, Palavras-chave: Microarrays, Anomalias congênitas, Atraso de desenvolvimento, Variante do número de cópia, Diagnóstico